Conceptualization of Grant of Justice Collaborator Status to Main Actors in Criminal Actions - Sulastri, Lusia (Journal of Law, Politic and Humanities, 2023)
The concept is not the main actor in determining Justice collaborators reap debate. This is because Richard Eliezer in the Brigadier J murder case was the main executor, even though he was the only person who was ordered to do so, but his position was that they were both perpetrators, but in fact it was accepted by the panel of judges. This research is aimed at examining the conceptualization of granting justice collaborator status to the main actors in criminal acts and the authority to grant justice collaborator status to the main actors in criminal acts. The results of the study state that the conceptualization of granting justice collaborator status to the main actors in criminal acts leads from the subjective pendulum to the objective pendulum. This means that so far the determination has been based on the subject, namely the main actor. However, with the rejections of Justice collaborator witnesses previously determined by the KPK or Prosecutors, the judge sees the objective actions of the perpetrators, this is what is called objective, no longer subjective whether the perpetrators themselves are the main actors or not. Determining the status of a justice collaborator who is awarded with a decision is the authority of the judge.